Enhancing women's empowerment as an effective strategy to improve food security in rural Bangladesh: a pathway to achieving SDG-2 - Sarker, Tanwne; Roy, Rana; Yeasmin, Sabina; Asaduzzaman, Muhammad (Frontiers in Sustainable Food Systems, 2024)
Introduction Women play an important role in maintaining household food security; unfortunately, their food security is frequently neglected. This type of phenomenon has become common in developing nations such as Bangladesh, particularly in its rural areas. The objective of this study is to investigate the variables that lead to the empowerment of rural women and its impact on their food security. In acknowledging women's significant contribution to achieving Sustainable Development Goal 2 (SDG-2)- Zero Hunger, this study investigates how access to resources, social support, and policy perceptions impact women's empowerment and food security. Methods A total of 480 rural women from the southern part of Bangladesh were questioned, and their responses were analyzed using partial least squares structural equation modeling. Results We found that access to resources, social support, and policy perceptions explain 74% of women's empowerment variance and women's empowerment explains 70% variance of women's food security. Access to resources and social support has significant positive impacts on women's empowerment. However, policy perceptions have a positive but not significant impact on women's empowerment. We also observed that women's empowerment significantly improved their food security. Practical implications To empower women and improve their food security, the accessibility of resources and support from social networks must be improved. The study emphasizes the importance of strengthening the government's policies, which aim to improve the livelihood conditions of vulnerable people through regular monitoring to overcome underlying obstacles. Our study offers empirical data that policymakers can use to address complex food affordability and security challenges during global crises, enabling the achievement of SDG-2 in rural areas of Bangladesh and similar societies.